USM CONTINUES TO ENHANCE INTERNATIONAL COMPETITIVENESS THROUGH COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, June 2015 Universiti Sains Malaysia (USM) will continue to enhance its global competitiveness by collaborating with renowned universities and institutions around the world either through research partnerships or offering of joint degrees.